Lik psa v zbirki Glasovi - Kovačič, Tanja (Studia mythologica Slavica, 2013)
The dog is not an interesting subject only for the Slovenian tradition, but it is known to all civilizations. Mythical dog usually acts as a companion of the gods and a guardian of the dead. Author of this paper questions which of these ideas have been preserved up to the twentieth century and how they have affect everyday life of people and their attitudes towards dogs in Slovenia. The mythological dog is investigated through the collection of Slovenian folk tales Glasovi. The author concludes that the dog is usually associated with mythical, superstitious and negative connotations and people included its positive character only rarely.
Keywords: mythology; oral literature; ljudsko slovstvo; mitologija; ethnology; dogs; folk literature; psi; Slovenia; Slovenija; etnologija